Kebijakan Pemerintah Daerah dalam Pelestarian Kesenian Tradisional di Kabupaten Jember - Widiyanto, Dayfrikoe (PUSKAPSI Law Review, 2021)
There are government policies to ensure the successful implementation of the concept of regional autonomy, once again a strong commitment and consistent leadership from the central government are needed. Law Number 23 of 2014 concerning Regional Government as amended several times, most recently by Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government ("Law No. 23 of 2014"). Preserving culture is closely related to what the independence of this nation has aspired to, namely the ideals to "educate the life of the nation" in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). The promotion of culture itself has been regulated in Law Number 5 of 2017 concerning the Advancement of Culture. In order to support the mandate of Law Number 5 of 2017 concerning the Advancement of Culture, it is necessary for the local government to contribute to realizing cultural sustainability in each Regency/City area. Based on this description, this research was conducted to find out the local government policies that have been carried out in order to preserve traditional arts in Jember Regency.